Developing Learning Innovative in The Metaverse World of a Computing Science Course at The Upper Primary Level - Suwannasri, Pimchanok; Suwannasri, Praisun; Monnoy, Thanet; Thiwong, Thawaree (Journal of Graduate Research, 2024)
The objectives of this research were to: 1) develop and evaluate the quality of learning innovation in the Metaverse world of the Computing Science course at the upper primary level; 2) compare students’ learning achievement before and after implementing the innovation; and 3) assess satisfaction towards implementation of the innovation. The sample group consisted of 47 primary 6 students from the Demonstration School of Chiang Mai Rajabhat University. The samples were obtained by using purposive sampling. Research instruments were: 1) Learning activities in the Metaverse world of the Computing Science course at the upper primary level, 2) Innovation quality assessment form, 3) Learning achievement test, and 4) Satisfaction assessment. Statistics used for analyzing data were mean, Standard Deviation, and t-test. The results revealed that learning innovations in the Metaverse world in the Computing Science course at the upper primary level consisted of multimedia, animated cartoons, interactive worksheets with answers, and AR skills practicing games. The result of the innovation quality assessment conducted by the experts was at the highest level, with a mean of 4.75 (S.D. = 0.30). The results of the comparison between the learning achievement of students before and after learning with innovation revealed that the mean of learning achievement after learning with innovation was higher than that of learning achievement before learning with innovation, with statistical significance at 0.05. Satisfaction with innovation implementation was high, with a mean of 4.02 (S.D. = 0.92).